Efektivitas Model Pembelajaran GQGA Dan ICM Terhadap Kemandirian Belajar Dan Prestasi Belajar Peserta Didik - Amral (Jurnal Riset Madrasah Ibtidaiyah, 2023)
This study aims to determine (1) whether the learning independence and learning achievement of students using the Giving Questions and Getting Answers (GQGA) learning model is better than the Index Card Match (ICM) learning model. (2) Is the learning model of Giving Questions and Getting Answers effective for class VIII students of SMP Muhammadiyah Nunukan? The data collection technique used is the method of documentation, observation, and tests. The research instrument was in the form of observation sheets and student achievement tests. The hypothesis test used was a multivariate test and continued with a separate univariate test. Based on the calculations, it can be concluded: (1) learning independence and learning achievement of students who are subjected to the Giving Question and Getting Answer learning model are better than learning independence and student achievement with the Index Card Match learning model. (2) learning with the Giving Question and Getting Answers learning model is effectively used for class VIII students of SMP Muhammadiyah Nunukan.